Patient participation during oncological encounters: Barriers and need for supportive interventions experienced by elderly cancer patients. Issue 12 (December 2017) - Noordman, Janneke; Driesenaar, Jeanine A.; Henselmans, Inge; Verboom, Jedidja; Heijmans, Monique; van Dulmen, Sandra
Highlights: Many elderly cancer patients feel confident in participating during encounters. 47% of patients experience communication barriers and need support. Barriers and facilitators relate to attributes of patients, providers or system. Experienced barriers and supportive interventions are not age-related. Abstract: Objective: To enhance patient participation during (oncological) encounters, this study aims to gain insight into communication barriers and supportive interventions experienced by elderly patients with cancer. Method: A mixed method design, including both quantitative (secondary survey data analysis) and qualitative (interviews) methods Survey data were used to identify communication barriers and need for supportive interventions of elderly cancer patients, compared to younger patients. Next, interviews provided in-depth insight into elderly patients' experiences and underlying mechanisms. Results: A majority of the 70 participating elderly cancer patients (53%) felt confident in communicating and participating during medical encounters. However, 47% of patients experienced barriers to effectively communicate with their healthcare provider and felt the need for supportive interventions. The 14 interviewed patients mentioned barriers and facilitators related to attributes of themselves (e.g. feeling sick, self-efficacy), the provider (e.g. taking patient seriously) and the healthcare system (e.g. time constraints). Conclusions: Although many elderly cancer patients feel confident, offering support to patients who feel less confident in communicating with their provider is recommended. Practice implications: The outcomes of this study can be used as a first step for developing interventions for elderly cancer patients to overcome communication barriers, and help providers to facilitate this process.